2004
DOI: 10.2337/diabetes.53.9.2195
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Adiponectin Receptor mRNA in Human Skeletal Muscle Cells Is Related to In Vivo Parameters of Glucose and Lipid Metabolism

Abstract: The adiponectin receptors, AdipoR1 and AdipoR2, are thought to transmit the insulin-sensitizing, anti-inflammatory, and atheroprotective effects of adiponectin. In this study, we examined whether AdipoR mRNA expression in human myotubes correlates with in vivo measures of insulin sensitivity. Myotubes from 40 metabolically characterized donors expressed 1.8-fold more AdipoR1 than AdipoR2 mRNA (588 ؎ 35 vs. 321 ؎ 39 fg/g total RNA). Moreover, the expression levels of both receptors correlated with each other (r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
73
0
7

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(93 citation statements)
references
References 32 publications
13
73
0
7
Order By: Relevance
“…In a study of a Mexican-American population, the expression levels of ADIPOR1 and ADIPOR2 in skeletal muscles and the plasma adiponectin concentration were lower in people with a family history of type 2 diabetes than in those without the family history [27]. This is consistent with the fact that the expression levels of both adiponectin receptors in human skeletal muscle cells were related to distinct in vivo parameters of glucose and lipid metabolism [28]. Genetic studies in an Old-Order Amish population also revealed that genetic variations in both adiponectin receptors, including the 5′ promoter regions, are associated with type 2 diabetes [29].…”
Section: Discussionsupporting
confidence: 68%
“…In a study of a Mexican-American population, the expression levels of ADIPOR1 and ADIPOR2 in skeletal muscles and the plasma adiponectin concentration were lower in people with a family history of type 2 diabetes than in those without the family history [27]. This is consistent with the fact that the expression levels of both adiponectin receptors in human skeletal muscle cells were related to distinct in vivo parameters of glucose and lipid metabolism [28]. Genetic studies in an Old-Order Amish population also revealed that genetic variations in both adiponectin receptors, including the 5′ promoter regions, are associated with type 2 diabetes [29].…”
Section: Discussionsupporting
confidence: 68%
“…Interestingly, we observed that refeeding carbohydrate did not change adipoR1 or adipoR2 expression in humans. Other studies in humans have shown that the adipoR1/R2 expression is not changed after insulin infusion (44) or after insulin addition to primary muscle culture (45). Together, these findings strongly suggest that adipoR expression is not regulated by glucose or insulin in humans.…”
Section: Figmentioning
confidence: 54%
“…Similarly, Inukai and colleagues [72] found that insulin had an inhibitory effect on AdipoR1 expression, in a mechanism mediated by the PI3K-dependent pathway rather than the MAPK pathway. In contrast to Inukai, Staiger and colleagues [73] reported that insulin did not directly modify AdipoR1 mRNA expression in human skeletal muscle cells. These discrepancies may be due to differences in animal model, cell types, or conditions used in these various studies.…”
Section: Interrelationship Between Insulin Signaling and Apn Signalingmentioning
confidence: 76%